Symbolic Meanings of Cooking in Enid Blyton’s The Famous Five Series - Wulandari, Retno; Pujiharto, Pujiharto; Cholsy, Hayatul (Anuva: Jurnal Kajian Budaya, Perpustakaan, dan Informasi, 2023)
Food and food preparation are the elements that usually reveals in works of literature. Its recurrent motif raises the assumption that they must contain some meanings in social and cultural realm. This paper analyses the symbolic meanings of cooking, as part of food preparation, in the British children work of literature, The Famous Five, written by Enid Blyton. The analysis uses theory of semiology proposed by Roland Barthes on denotative and connotative meanings and it is conducted through close-reading. The analysis results in how cooking becomes: first, a routine obligation, where the women cook mostly spend their time doing their work in the kitchen and work orderly to please; second, cooking as a marker of maturity for coming-of-age girls, in which teenage becomes the time marker that a girl must be able to cook; third, cooking as a marker of gender-based job division, where women should involve in domestic works, while men dedicate in public sphere. The children’s literature becomes one of the effective tools to embed the values and beliefs in children’s mind as childhood is the golden age to receive any information through the children’s senses.